COMPARISON OF FIVE EXTERNAL PARAMETERS IN ASSESSING THE AIRWAY: A PROSPECTIVE COMPARATIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Aim & Objective: This study aims to determine the single predictor, which is more sensitive, specific and has higher positive predictive value in predicting difficult airway. Material and Methods: A total of 90 patients who are scheduled to undergo elective surgery under general anesthesia are selected. Pre-operative airway examination was performed using MMP, TMD, and Neck circumference, NC/TMD to predict difficult intubation. After induction of the general anesthesia laryngoscopy was performed, view on laryngoscopy was graded using the classification of Cormack and Lehane. A note was also made of whether or not intubation was difficult that is if the view at laryngoscopy was grade III or IV even in patients who were predicted to have easy intubation using multiple screening tests. If difficulty was experienced in tracheal intubation, backward, upward and rightward pressure on thyroid cartilage, BURP was applied as it improved visualization of glottis on direct laryngoscopy.   Endotracheal intubation was considered truly difficult (observed difficult), if any of the following were positive. 1. Cormack and Lehane glade III and IV, 2. Three attempts at tracheal intubation or duration longer than ten minutes, 3. If special maneuvers were used to facilitate tracheal intubation which in our study fiber-optic intubation. 4. Failure to intubate. Rest of the patients were considered to have truly easy. [Observed easy] endotracheal intubation. Results: By comparing all five parameters, TMD to NC ratio has the highest accuracy (90%) with 89.3% of sensitivity and 90.3% of specificity. Conclusion: The study indicated that NC/TMD as simple preoperative bedside tests have a higher level of accuracy compared to TMD, NC, MMP, and BMI in predicting a difficult airway.